Influence of Different Pigmentations and Accelerated Aging on the Hardness and Tear Strength of the A-2186 and MDX4-4210 Silicones - Estefânia Marrega Malavazi; Daniela Micheline dos Santos; Clóvis Lamartine de Moraes Melo Neto; Fernanda Pereira de Caxias; Emily Vivianne Freitas da Silva; Lisiane Cristina Bannwart; Aldiéris Alves Pesqueira; André Luiz de Melo Moreno; André Pinheiro de Magalhães Bertoz; Marcelo Coelho Goiato (International Journal of Dentistry)
Objective. To evaluate the influence of different pigmentations and accelerated aging on the hardness and tear strength of the A-2186 and MDX4-4210 silicones. Materials and Methods. The samples A-2186 and MDX4-4210 were manufactured without and with pigmentations (black, bronze, and pink). For the Shore A hardness test, 80 samples of each silicone were fabricated, and for the tear strength test, 320 samples of each silicone were fabricated. Eight groups were created for each test (n = 10). These tests were performed before and after 252, 504, and 1008 hours of aging. Three-way repeated-measures analysis of variance and the Tukey test were performed (α = 0.05). Results. The A-2186 silicone showed higher hardness and tear strength when compared with the MDX4-4210 silicone p<0.05, except in the hardness of the A-2186 and MDX4-4210 groups without pigmentation after 1008 hours p>0.05. All hardness values were between 25 and 35 units, regardless of the silicone type, period, and pigmentation (or no pigmentation). In most situations, the hardness of silicones used increased after 252 hours p<0.05. The nonpigmented MDX4-4210 group and all A-2186 groups showed an increase in tear strength after 252 hours p<0.05. For the nonpigmented MDX4-4210 group, from 252 to 1008 hours, there was no change in tear strength p>0.05. All pigmented MDX4-4210 groups showed no change in tear strength from 0 (initial) to 1008 hours of aging p>0.05. In all A-2186 groups, from 252 to 504 hours, there was a reduction in tear strength p<0.05, and from 504 to 1008 hours, there was an increase in tear strength p<0.05, except in the bronze A-2186 group p>0.05. Conclusion. In most situations, the A-2186 silicone showed significantly higher values of hardness and tear strength than the MDX4-4210 silicone. All hardness values were considered clinically acceptable. Accelerated aging could increase, decrease, or not significantly change the hardness and tear strength of the silicones used. The results of hardness and tear strength suggest that MDX4-4210 was more influenced by the presence of pigmentation after aging.